POEMS Syndrome Diagnosed 10 Years after Disabling Peripheral Neuropathy - Viet H. Nguyen (Case Reports in Medicine)
Peripheral neuropathy is characterized as a generalized, relatively homogeneous process affecting many peripheral nerves and predominantly affecting distal nerves. The epidemiology of peripheral neuropathy is limited since the disease presents with varying etiology, pathology, and severity. Toxic, inflammatory, hereditary, and infectious factors can cause damage to the peripheral nerves resulting in peripheral neuropathy. Peripheral neuropathy is most commonly caused by diabetes, alcohol, HIV infection, and malignancy. We report a case of a 42-year-old female with 10-year history of progressively worsening peripheral neuropathy, hypothyroidism, and skin changes who presents with dyspnea secondary to recurrent pleural and pericardial effusions. Prior to her arrival, her peripheral neuropathy was believed to be secondary to chronic demyelinating inflammatory polyneuropathy (CDIP) given elevated protein in the cerebral spinal fluid (CSF) which was treated with intravenous immunoglobulin (IVIG) and corticosteroids. Unfortunately, her peripheral neuropathy did not have any improvement. Incidentally, patient was found to have splenomegaly and papilledema on physical exam. Serum protein electrophoresis showed a monoclonal pattern of IgA lambda. Patient met the diagnostic criteria for POEMS (polyneuropathy, organomegaly, endocrinopathy, M-protein, and skin changes) syndrome. An underlying diagnosis of POEMS syndrome should be considered in patients with chronic debilitating neuropathy and an elevated protein in the CSF.